Control orchestration protocol: Unified transport API for distributed cloud and network orchestration - Mayoral, Arturo; Vilalta, Ricard; Munoz, Raul; Casellas, Ramon; Martinez, Ricardo; Moreolo, Michela Svaluto; Fabrega, Josep M.; Aguado, Alejandro; Shuangyi Yan; Simeonidou, Dimitra; Gran, Jose M.; Lopez, Victor; et al. (Journal of Optical Communications and Networking, 2017)
In the context of the fifth generation of mobile technology (5G), multiple technologies will converge into a unified end-to-end system. For this purpose, software defined networking (SDN) is proposed, as the control paradigm will integrate all network segments and heterogeneous optical and wireless network technologies together with massive storage and computing infrastructures. The control orchestration protocol is presented as a unified transport application programming interface solution for joint cloud/network orchestration, allowing interworking of heterogeneous control planes to provide provisioning and recovery of quality of service (QoS)-aware end-to-end services. End-to-end QoS is guaranteed by provisioning and restoration schemes, which are proposed for optical circuit/packet switching restoration by means of signal monitoring and adaptive modulation and adaptive route control, respectively. The proposed solution is experimentally demonstrated in an international multi-partner test bed, which consists of a multi-domain transport network comprising optical circuit switching and optical packet switching domains controlled by SDN/OpenFlow and Generalized Multiprotocol Label Switching (GMPLS) control planes and a distributed cloud infrastructure. The results show the dynamic provisioning of IT and network resources and recovery capabilities of the architecture.